Reusability, Long‐Life Storage and Highly Sensitive Zirconium Nitride (ZrN) Surface‐Enhanced Raman Spectroscopy (SERS) Substrate Fabricated by Reactive Gas‐Timing Rf Magnetron Sputtering - Nguentra Sucheewa; Winadda Wongwiriyapan; Prapakorn Rattanawarinchai; Tuksadon Wuttikhun; Kittiphat Sinthiptharakoon; Saran Youngjan; Pongtanawat Khemthong; Gamolwan Tumcharern; Tossaporn Lertvanithphol; Nutthamon Limsuwan; Apirak Pankiew; Mati Horprathum; et al. (Advanced Materials Interfaces, 2023)
Abstract Transition metal nitrides (TMN) are promising material alternative to replace noble metals in the field of plasmonic applications, especially surface‐enhanced Raman spectroscopy (SERS). Here we demonstrate a practical surface enhanced Raman spectroscopy (SERS) substrate using zirconium nitride (ZrN) thin films grown by reactive gas‐timing (RGT) rf magnetron sputtering. The tailored properties of ZrN thin film exploited for SERS activity could be achieved to obtain a highly sensitive ZrN thin film SERS substrate with the enhancement factor (EF) of 1.24 × 106 and 4.8 %RSD at 1626 cm‐1 toward methylene blue (MB) analyte which are comparable to the optimized Au sputtered thin films (EF=1.18 × 106 and with 5.1%RSD). We find that the spatial plasmonic hotspots on the surface of ZrN SERS substrate controlled by the turn‐on timing of Ar:N2 sputtered gas sequence, leading to the discrete conductive surface profile, strongly relates to non‐stoichiometric composition and the degree of (200)‐oriented texture at the surface of ZrN thin film. Furthermore, ZrN thin film SERS substrates exhibit an excellent recyclability more than 30 cycles with simple cleaning process and a storage time longer than 6 months. The detection and reusability of ZrN SERS substrate on the low concentration of trinitrotoluene (TNT) for homeland security are also performed.
Keywords: Gold and Silver Nanoparticles Synthesis and Applications; Spectroscopy Techniques in Biomedical and Chemical Research; Plasmonic and Surface Plasmon Research